Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and the Yahoo Answers website is now in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Solve the system by addition 2x – 9y = 4 x – 2y = –3?
3 Answers
- Anonymous1 decade agoFavorite Answer
2x - 9y = 4
-2x + 4y = 6
-5y = 10
y = -2
x = -7
- ?Lv 71 decade ago
2x-9y=4
x-2y=-3
Multiply the second equation by -2
2x-9y=4
-2x+4y=6
-------------Add
-5y=10
y=-2
Substitute -2 for y back into either original
equation. I'll use the first.
2x-9(-2)=4
2x+18=4
2x=4-18
2x=-14
x= -7
Check:
2x-9y=4
2(-7)-9(-2)=4
-14+18=4
4=4
x-2y=-3
-7-2(-2)=-3
-7+4=-3
-3=-3
We're done. the answers are correct
- Anonymous1 decade ago
2x - 9y = 4
x - 2y = - 3 (multiply this line by -2)
-2x + 4y = 6
Solve by addition...
9y - (+4y) = 4 + 6
therefore -5y = 10 or y = -2
by substitution... if y = - 2 then x = -7